JORDAN LANDES and RICHARD ESPLEY, eds., Radical Collections: Re-Examining the Roots of Collections, Practices and Information Professions - Grant, Jennifer (Archivaria, 2019)
Radical Collections: Re-Examining the Roots of Collections, Practices and Information Professions. Jordan Landes and Richard Espley, eds. London: Senate House Library, 2018. xii, 82 pp. ISBN 978-1-913002-01-5